HUBUNGAN ANTARA MOTIF BERPRESTASI, MOTIF BERAFILIASI, DAN MOTIF BERKUASA DENGAN DISIPLIN TATA TERTIB SEKOLAH - AGUS SUHARNO (DIMENSI PENDIDIKAN, 2005)
The main concern of this study was to find out : (1) the corelation between achievement motive, affiliation motive, power motive, and school disipline; (2)?é?áthe corelation between achievement motive and school disipline; (3)?é?áthe corelation between affiliation motive and school disipline; (4)the corelation between power motive and school disipline. The subject of this study were 320 second grade students of state senior high school. The study was conducted in the third semester of 1995/1996. Questionnaire, and documentation were used for collecting data. The data were analyzed by regession analysis and partial correlation. The results of the study were as follows : (1) There was significant correlation between achievement motive, affiliation motive, and power motive and shool disipline; (2) There was a positive relation between achievement motive and school disipline; (3) There was a positive relation between affiliation motive and school disipline; (4) There was negative relation between power motive and school disipline. Keyword : achievement motive, affiliation motive, power motive, shool disipline